Analysis of the impact of the tax burden on taxpayers in Uzbekistan - Suyunov Axmadjon Xujamurodovich (Genius Journals, 2024)
The article theoretically examines the importance of the indicator of the tax burden in the economy, the problems of its determination, various opinions of domestic and foreign scientists on determining the optimal levels of the tax burden in the economy, scientific conclusions and proposals are formulated, and directions for calculating the tax burden in legal entities and individuals are provided.
Keywords: Tax burden; optimal tax burden; tax rates; state budget expenditures